3D Amide Proton Transfer Weighted Brain Tumor Imaging With Compressed SENSE: Effects of Different Acceleration Factors - Zhang, Nan; Zhang, Haonan; Gao, Bingbing; Miao, Yanwei; Liu, Ailian; Song, Qingwei; Lin, Liangjie; Wang, Jiazheng (Frontiers in Neuroscience, 2022)
Abstract Objectives The aim of the current study was to evaluate the performance of compressed SENSE (CS) for 3D amide proton transfer weighted (APTw) brain tumor imaging with different acceleration factors (AF), and the results were compared with those by conventional SENSE. Methods：51 brain tumor patients (22 males, 49.95±10.52 years) with meningiomas (n=16), metastases (n=12), or gliomas (n=23) were enrolled. All patients received 3D APTw imaging scans on a 3.0 T scanner with acceleration by CS (AFs: CS2, CS3, CS4, and CS5) and SENSE (AF: S1.6). Two readers independently and subjectively evaluated the APTw images relative to image quality and measuring confidence with respect to image blur, distortion, motion and ghosting artifacts, lesion recognition and contour delineation with a 5-point Likert scale. Mean APT values of brain tumors (APTtumor), the contralateral normal appearing white matter (APTCNAWM), and the peritumoral edema area (if present, APTedema), and the tumor volume (VAPT), were measured for objective evaluation and determination of the optimal AF. The Ki67 labeling index was also measured by using standard immunohistochemical staining procedures in samples from gliomas patients, and correlation between tumor APT values and Ki67 index was analyzed. Results The image quality of AF=CS5 was significantly lower than that of other groups.VAPT showed significant differences among the six sequences in meningiomas (p = 0.048) and gliomas (p = 0.023). The pairwise comparison showed that the VAPT values of meningiomas measured from images by CS5 were significantly lower and gliomas were significantly larger than those by SENSE1.6 and other CS accelerations, (p < 0.05). APTtumor (p=0.191) showed no significant difference among the three types of tumors. the The APTtumor values of gliomas measured by APTw images with SENSE factor of 1.6 and CS factor of 2, 3, and 4 (except for CS5) were all positively correlated with Ki67. Conclusion Compressed SENSE could be successfully extended to accelerated 3D APTw imaging of brain tumors without compromising image quality using the AF of 4.